Are massive open online courses (MOOCs) pedagogically innovative? - Armellini, Alejandro; Padilla Rodríguez, Brenda Cecilia (National Center for Online Learning Research, 2016)
While claims about pedagogic innovation in Massive Open Online Courses (MOOCs) are common, most reports provide no evidence to justify those claims. This paper reports on a survey aimed at exploring how different stakeholders describe MOOCs, focusing on whether they would consider them pedagogically innovative, and if so, why. Respondents (n = 106) described MOOCs primarily as free, openly accessible online courses that attract large numbers of participants. Views on pedagogic innovation fell into three categories: 1) MOOCs are pedagogically innovative (15.1%). Explanations referred to the massiveness, openness and connectivism. None of the participants offered a clear definition of or criteria for pedagogic innovation. 2) MOOCs are not pedagogically innovative (84.9%). More than half of the respondents added an unsolicited opinion, including strong criticisms of MOOCs. 3) MOOCs may or may not be pedagogically innovative. The evidence suggests that caution should be exercised when characterising MOOCs as pedagogically innovative.